Recent investigations of the near-Mars space environment by the planetary aeronomy and space physics community in China - Jun Cui; ZhaoJin Rong; Yong Wei; YuMing Wang (Earth and Planetary Physics, 2020)
The present issue of Earth and Planetary Physics is dedicated to the near-space neutral and plasma environments of Mars. The issue includes nine papers that present new results on the properties of the Martian exosphere, ionosphere, and magnetosphere, from both observational and modeling points of view. Due to the similarity between the two objects, the issue also includes two additional papers on the near-Venus plasma environment.